Qur’anic-Based Educational Leadership: An Inquiry Into Surah Al-Fatihah - Dakir, Dakir; Fauzi, Ahmad (Nadwa: Jurnal Pendidikan Islam, 2020)
The study of leadership has become an important part amid a multidimensional crisis and a decline in morality in various leadership settings; the significance of this leadership influences the organizational system's sustainability. Thus, this research study aims to build a portrait of Islamic education leadership as an ideal leadership model through the internalization of al-Fatihah's values. This study aims to unpack Islamic school leadership values and principles from al Fatihah verses as an ideal leadership model by internalizing al-Fatihah's values. The findings suggest a) Surah al Fatihah contains Islamic school leadership value derived from rabbaniyah value (monotheism) and Insaniyah value (relationship with others). b) changing Islamic school leadership paradigm from indoctrination to active participation. This study demonstrates that all Islamic education organizations should act by inspiring without indoctrination, awakening without hurting, and arousing without forcing.